Letters from the Cork Brigade, Irish Volunteers, relating to Volunteer barracks in Cork and regarding conflict with Cumann na mBan over the use of City Hall - Irish Volunteers. Cork Brigade; O'Donoghue, Florence, 1895-1967; Ní Bhriain, Nóra; O'Hegarty, Seán, 1881-1963 (1918)
Includes letter from Nóra Ní Bhriain, Honorary Secretary, seeking permission to use the Hall for a Céilidhe to be held following the Irish Volunteers' Concert, and letter from Seán O'Hegarty outlining the situation to the [Brigade Commandant]
Keywords: Irish Volunteers. -- Cork Brigade; Cumann na mBan -- Correspondence; Ireland -- History -- 1910-1921